Biomechanical alteration in table tennis and tennis sports players: a systematic review - Hitansha; Das, J.; Aditi (European Journal of Applied Physiology, 2025)
Background Biomechanical alterations, including changes in shoulder mechanics, lower limb function, and visual-motor coordination, play a crucial role in influencing both performance and injury risk among table tennis players. Understanding these adaptations is essential for developing effective training protocols and injury prevention strategies.